AB0009 Association of an HLA-G 3'UTR haplotype with susceptibility to rheumatoid arthritis: A north-south analysis in two independent brazilian cohorts. (23rd January 2014) - Veit, T.D.; de Lima, C.; Brenol, C.; Brenol, J.C.; Ribeiro, A.; Correa, R.; Cavalheiro, L.; dos Santos, E.; Xavier, R.; Chies, J.A.
Abstract : Background: HLA-G may exert long-term immunotolerogenic effects through the generation of suppressor cells [reviewed in [1]]. Such features render HLA-G an attractive candidate gene for susceptibility to immune mediated diseases. Indeed, our group has observed a positive association of a 3'UTR haplotype encompassing the 14bp locus and the +3142C/G (rs1063320) and disease susceptibility in patients with systemic lupus erythematosus [2]. Objectives: To investigate the genetic influence of the two HLA-G 3'UTR polymorphisms – the 14 bp insertion/deletion (rs1704) and the +3142C>G (rs1063320) – in the susceptibility to rheumatoid arthritis in a double-center study comprising a Southern-Brazilian cohort from Porto Alegre and Northern-Brazilian cohort from the city of Belém. Methods: A total number of 546 RA patients and 531 controls was PCR genotyped for the two polymorphisms. Results: Haplotype frequencies differed significantly between control groups from the Northern and Southern cohorts. After adjusting for city of origin and gender, we observed that female patients presented a higher frequency of the deletion-G (D/G) haplotype (OR=1.634, 95% CI=1.128–2.368, P=0.009). After stratifying for RF positivity, only the female RF+ group of patients presented statistical significance (OR=1.829, 95%C.I =1.243–2.690, P=0.002) - Table 1 . Conclusions: Our results suggest a differential influence of HLA-G 3'UTR polymorphisms in disease susceptibility, with the D/G haplotype as a risk factor for RA in RF+ females. References: Carosella ED, HoWangYin K-Y, Favier B, LeMaoult J. Hla-g-dependent suppressor cells: Diverse by nature, function, and significance. Human immunology 2008;69:700-7. Consiglio CR, Veit TD, Monticielo OA, et al. Association of the hla-g gene +3142c>g polymorphism with systemic lupus erythematosus. Tissue Antigens 2011;77:540-5. Disclosure of Interest: None Declared